Policies to Mitigate Procyclicality. (IMF Staff Position Notes; Staff Position Note ;, 2009)
This paper examines the reasons for this, specifically focusing on regulations or market practices that can accentuate economic cycles. Although recognizing various practical limitations, new policy responses are identified that could help to mitigate procyclicality. Although economic cycles are taken as a natural and recurring phenomenon, there are ways in which private sector behavior and practices, prudential regulation, and macroeconomic policies can act to magnify such cycles. A key challenge for policymakers will be to counter the exacerbating effects of prudential regulations while at the same time keeping the risk-based decision-making processes that are increasingly used in the private sector. Procyclicality is also embedded in credit risk management systems and guidelines, because the inputs (default probabilities, loss severities, default correlations, and credit ratings) tend to vary positively with economic cycles. Credit ratings are supposed to be assigned on a 'through-the-cycle' basis, and not according to transitory fluctuations in credit quality.